Strain engineering and electric field tunable electronic properties of Ti2CO2 MXene monolayer. (27th March 2019) - Pham, Khang D; Hieu, Nguyen V; Bui, Le M; Ershov, Igor V; Hieu, Nguyen N; Phuc, Huynh V; Hoi, Bui D; Phuong, Le T T; Duc, Le M; Idrees, M; Amin, Bin; Nguyen, Chuong V
Abstract: In this work, we investigate theoretically the structural and electronic properties of the monolayer Ti2 CO2 MXene using first-principles calculations. At the ground state, the monolayer Ti2 CO2 MXene structure is dynamically stable and is a semiconductor with an indirect band gap of 0.75 eV, which can be controlled by strain engineering and electric field. We find that the indirect band gap of the monolayer Ti2 CO2 MXene could be transformed into a direct one. Whereas, a semiconductor–metal transition can be achieved by applying the compressive biaxial strain of −10%. Our results demonstrate that the monolayer Ti2 CO2 MXene can be a potential material for designing optical nanodevices with the strain engineering and electric field tunable of the band gap.